Conceptualization of Participation: A Qualitative Synthesis of Brain Injury Stakeholder Perspectives - Rajala, Caitlin; Waterhouse, Camden; Evans, Emily; Erler, Kimberly S.; Bergin, Michael J.; Bannon, Sarah M.; Slavin, Mary D.; Kazis, Lewis E. (Frontiers in Rehabilitation Sciences, 2022)
Background The return to participation in meaningful life roles for persons with acquired brain injury (pwABI) is a goal shared by pwABI, their families, clinicians, and researchers. Synthesizing how pwABI define participation will help to identify the aspects of participation important to pwABI and can inform a person-centered approach to participation outcome assessment. To-date, the qualitative synthesis approach has been used to explore facilitators and barriers of participation post-stroke, and views about participation among individuals with stroke in the UK. Objectives This paper's objectives are to (1) conduct a scoping review of qualitative literature that defines and characterizes participation from the perspective of pwABI of any type, (2) synthesize how pwABI define and categorize participation, and (3) link the themes identified in the qualitative synthesis to the International Classification of Functioning, Disability, and Health (ICF) using standardized linking rules to enhance the comparability of our findings to other types of health information, including standardized outcome measures. Methods We completed a scoping review of qualitative literature. Our search included PubMed, APA PsychInfo, CINAHL, and Embase databases and included articles that (1) had qualitative methodology, (2) had a sample ≥50% pwABI, (3) had aims or research questions related to the meaning, definition, perception, or broader experience of participation, and (4) were in English. Qualitative findings were synthesized using Thomas and Harden's methodology and resultant themes were linked to ICF codes. Results The search identified 2,670 articles with 2,580 articles excluded during initial screening. The remaining 90 article abstracts were screened, and 6 articles met the full inclusion criteria for the qualitative synthesis. Four analytical themes emerged: (1) Essential Elements of Participation (2) How pwABI Approach Participation, (3) Where pwABI Participate, and (4) Outcomes of Participation. Each overarching theme included multiple descriptive themes. Conclusion In this paper, we identified themes that illustrate key components of participation to pwABI. Our results provide insight into the complex perspectives about participation among pwABI and illustrate aspects of participation that should hold elevated importance for clinicians and researchers supporting participation of pwABI.